PEMETAAN LOKASI GEDUNG SEKOLAH MENENGAH ATAS DAN SEKOLAH MENENGAH KEJURUAN NEGERI DI KOTA SURABAYA MENGIKUTI DENGAN ADANYA ZONASI BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) - Revaldi, Tio Kresna (Jurnal Vokasi Teknik Sipil, 2023)
This research aims to determine the mapping and distribution pattern of locations of foreign language course institutions in English villages using a geographic information system (GIS). This research is quantitative research and the samples in this research are State High Schools with a total of 22 schools, and State Vocational Schools with a total of 13 schools spread widely in the Surabaya City area. The data collection technique used is field observation to determine the coordinate points (X, and Y) of State High Schools and State Vocational Schools in the Surabaya City area, Observation via the official Institution website of the Surabaya City Education Service to find out the systematic PPDB Zoning route, and the official Institution website Department of Population and Civil Registration in the City of Surabaya to find out the number of students aged 15 - 19 years at the State High School and State Vocational School levels. The method used is descriptive analysis to create a location distribution map for State High Schools and State Vocational Schools using Arcgis 10.8 software, nearest neighbor analysis to find location distribution patterns by calculating the T value or nearest neighbor distribution index. The calculated T value is 1.09 which is included in the even pattern for State High Schools, and 1.56 for State Vocational Schools which is included in the uneven pattern.